On P, NP, and Computational Complexity. - Vardi, Moshe Y. (Communications of the ACM, 2010)
The article examines the significance of a blog posted by computer science blogger Richard Lipton wherein he argued the validity of a major proof in computational mathematics. Lipton made comments on the P versus NP quandary, an algorithmic theorem central to computer science. He claimed that P is not equal to NP, as has previously been believed. Also discussed are the implications that this has for computer programming.